Certified Blockchain Developer--Hyperledger Fabric (CBDH) - Holbrook, Joseph (Pearson IT Certification, 2019)
7+ Hours of Video Instruction Overview More than 7 hours of video instruction to prepare you to pass the Certified Blockchain Developer-Hyperledger Fabric (CBDH) exam and develop your skills in the emerging and in-demand blockchain arena. Overview In Certified Blockchain Developer-Hyperledger Fabric (CBDH) Complete Video Course, seasoned IT veteran and current blockchain subject matter expert, Joseph Holbrook, provides an in-depth exploration of developing blockchain solutions, which are quickly becoming the de facto, decentralized method for verifying and tracking cryptocurrency and other digital transactions. While the primary objective of this LiveLessons video course is to provide you with all of the information you need to prepare for and pass the Blockchain Training Alliance CBDH exam, the course also delves into planning and preparing production-ready applications for the Hyperledger blockchain; learning how to work effectively with blockchain engineers and technical leaders; select appropriate Hyperledger blockchain systems for various use cases; and write, test, and deploy secure chain code. Whether you are seeking to gain the CBDH certification or simply looking to enhance your blockchain development skills, Joseph Holbrook's instruction through deep-dive discussion, whiteboarding analysis, and practical demos will ensure that you boost your confidence and skills in working with this burgeoning disruptor approach to digital transactions. The Certified Blockchain Solution Architect (CBDH) exam is an elite way to demonstrate your knowledge and skills in this emerging space. Additionally, you will become a member of a community of Blockchain leaders. About the Instructor Joe Holbrook has been in the IT field since 1993 when he was exposed to several HPUX systems on board a US Navy flagship. He has migrated from UNIX world to Storage Area Networking (SAN) and Enterprise Virtualization and Cloud Architectures and now specializing in Blockchain and Cryptocurrency. He previously worked for numerous companies like HDS, 3PAR, Brocade, HP, EMC, Northrup Grumman, ViON, Ibasis.net, Chematch.com, SAIC and Siemens Nixdorf. He also has been a published course author on Linkedin Learning, Udemy.com, INE.com and Pearson Safari. He is also author of a new book due to be released in early 2019 on "Architecting Enterprise Blockchain Solutions" Currently he is a recognized industry expert specializing in Enterprise Cloud and Blockchain Technologies. He ...